The Effect of Environmental Management Accounting and Business Strategy on the Sustainable Production Effectiveness of SMEs in Toraja - Olivia Devi Yulian Pompeng; Astriwati Biringkanae (LP2M IAIN Palopo, 2026)
Environmental Management Accounting (EMA) is an appropriate approach to support decision-making that considers both economic and environmental aspects simultaneously (Hutagalung & Lumban, 2024; Fitriani & Pandin, 2025; Setiawan & Ghozali, 2016). Increasing competition in the business world forces entrepreneurs to adopt effective strategies and continuously innovate their products to remain competitive and meet customer needs (Kotler & Keller, 2016). Sustainable production effectiveness is measured using indicators such as resource use efficiency, regulatory compliance, waste reduction, and customer satisfaction. The study employed a quantitative approach. Data were collected through the distribution of questionnaires to culinary and craft SMEs in Toraja. Data analysis techniques included validity and reliability tests, as well as linear regression analysis to determine the significance of the influence of the independent variables (EMA and business strategy) on the dependent variable (sustainable production). The results of the study indicate that both EMA and business strategy significantly affect sustainable production in SMEs in Toraja.